Perspektif Balanced Scorecard Terhadap Kinerja Sekolah di SDIT Lentera Hati - Choirul Amin; Suad Suad; Santosa Santosa; Sri Utaminingsih (Manajemen Pendidikan, 2020)
The purposes of this study are: 1) describe the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from a financial perspective, 2) describe the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from a customer perspective, 3) describe the performance of the SDIT Lentera Hati based on the Balanced Scorecard approach from an internal business perspective , and 4) describe the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from the perspective of learning and growth. This research is quantitative descriptive research type. Research data obtained through questionnaires, interviews, and documentation. The research sample was taken from the population of teachers and parents/guardians of students as many as 20 teachers and 130 parents/students guardians. The results showed that 1) the performance of SDIT Lentera Hati based on Balanced Scorecard approach from a financial perspective by 60% in the good category, 2) the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from the customer perspective by 80% in the good category, 3) the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from an internal business perspective by 82% in the excellent category, 4) the performance of SDIT Lentera Hati based on the Balanced Scorecard approach from a learning and growth perspective by 80% in the good category.